Effectiveness of Disaster Education Programs in Senior High Schools: A Study of Implementation and Impact in Indonesia, China, The Philippines and Thailand - syam, Ilham; Thamrin, Yahya; A. Arsunan Arsin; Muhammad saleh, Lalu; Maulana, Adi; Khuzaimah, Ana; Manyullei, Syamsuar (Journal of Neonatal Surgery, 2025)
Background: Disasters are unavoidable emergencies that will be difficult to handle by those affected, especially without outside assistance. Disaster preparedness is a real necessity in this country, especially for earthquakes. Objective: Review research related to disaster management in school children in the four countries of Indonesia, China, Thailand, and the Philippines, with Thailand having the least knowledge of disaster management. Methods: Study analysis through 5 electronic databases (pubemed, since direct, google scholar, connective paper, and Scopus). In the first stage 65 articles, at the last search there were 9 studies included. Results: The Philippines implemented a disaster risk reduction management (DRRM) curriculum program incorporated in the Philippine Act of 2010 into the school curriculum. Indonesia developed a disaster management mobile application program, and Indonesia implemented the SSSB instrument program. China implemented a geography curriculum program that includes geography as a compulsory course in schools. Thailand implemented the school safe community (SSC) program. Conclusion: Disaster education in senior high schools is important to build a culture of safety and resilience. School preparedness in the face of natural disasters is crucial. Disaster impacts include casualties, environmental damage, and psychological effects that need to be considered.